Model Manajemen Publik dalam Tata Kelola Dewan Adat Minahasa Berbasis Living Law Untuk Penguatan Masyarakat Hukum Adat - Michael Spink Rumondor (Madani: Jurnal Ilmiah Multidisiplin, 2026)
The background of this research is the gap between constitutional recognition of indigenous peoples as mandated by Article 18B paragraph (2) of the 1945 Constitution of the Republic of Indonesia and the suboptimal governance of customary institutions at the regional level. This qualitative research employs a case study method on the Minahasa Customary Council, collecting data through document study on the draft articles of association and bylaws of the Minahasa Customary Council for the year 2025, the academic manuscript of the regional regulation draft, and various relevant laws and regulations. The findings reveal that the Minahasa Customary Council has a robust organizational structure by adopting the Trias Politica Adat principle, which divides power among the Plenary Assembly of Custom, the Joint Secretariat of Custom, and the Customary Court and Council of Elders. However, this institution faces significant obstacles due to the absence of legal umbrella at the regional level, as the regional regulation draft on the establishment of the Minahasa Customary Council and Customary Court remains stalled in academic manuscript status. This study formulates a Public Management Model for Minahasa Customary Council Governance Based on Living Law, integrating three main pillars, namely strengthening organizational structure through institutional formalization and procedural standardization, developing human resource management through competency-based recruitment systems and regeneration programs, and performance-based financial management through customary accounting standardization and the establishment of the Customary Financial Audit Board. This model integrates Minahasa's living law values, namely Si Tou Timou Tumou Tou, Mapalus, Maesaan, Kasuruan, and Tonaasan, with good governance principles.